Barnacle Goose Branta leucopsis abundance on Kolguev Island â€“ current status and history of population growth - Kondratyev, Alexander; Zaynagutdinova, Elmira; Kruckenberg, Hulmut (Wildfowl, 2013)
Barnacle Geese Branta leucopsis first colonised the Russian arctic island of Kolguev inÂ the early 1980s, since when their numbers have steadily grown. Initial colonies wereÂ founded on fox-free coastal sand spits, but by the mid-1990s large colonies (> 5,000Â breeding pairs) had become established in the Peschanka River delta, reaching 45,000Â breeding pairs by the mid-2000s. Subsequently, numerous new smaller colonies (mean Â± s.d. = 12 Â± 6 nesting pairs, range = 1â€“54, n = 18 colonies) started to increaseÂ in numbers in the central part of the island, initially associated with c. 30% of allÂ known Peregrine Falcon Falco peregrinus nests in the study area. The overall populationÂ size and number of inland colonies continued to grow, and by 2011â€“2012 all 24Â known Peregrine Falcon nests had Barnacle Goose colonies (mean colony size = 54Â Â± 40 pairs, range = 1â€“133, n = 13 colonies). White-fronted Geese Anser albifrons andÂ Tundra Bean Geese Anser fabalis rossicus formerly recorded nesting in dense coloniesÂ around Peregrine Falcon nests no longer did so, apparently having been expelledÂ from core areas by the earlier nesting and more aggressive Barnacle Geese. TheÂ hatching success of Barnacle Geese nesting in the open sedge-moss bogs of centralÂ Kolguev (first occupied in 2011â€“2012) was no different to those associating withÂ Peregrine Falcons (73% and 75% respectively). During brood rearing and moulting,Â Barnacle Geese share feeding habitats with other goose species. Should theirÂ numbers continue to grow on the island, further overgrazing of foraging habitats may increase competition between Barnacle Geese and White-fronted Geese forÂ food, both in brood-rearing and in moulting habitats.